Levels of Discomfort: Paul Beatty’s The Sellout as the First American Novel to Win the Man Booker Prize - Friedrich, Judit (Hungarian Journal of English and American Studies, 2020)
The essay explores the context in which the first American novel won the British Booker Prize. Paul Beatty’s novel was hailed as a comic masterpiece. The essay discusses how comedy works in this novel, how the book fits the profile of the Man Booker Prize, and how the work reads against the tradition of the English comic novel. The Sellout (2015) shows elements of standup comedy, delivered in a deadpan voice, yet referencing the latest social and intellectual theories. The topic is the silent erasure of a predominantly black community in the greater Los Angeles area, and its politically incorrect resuscitation. The novel creates an eerie feeling of being set in a vast emptiness, yet indicates a recognizable location in the congested Los Angeles area, moving between desperate satire and magic realism, with an intellectual freedom created by the level acceptance and unflinching description of the cognitive dissonances of the world depicted.